SAFE to Update Inflation Expectations? New Survey Evidence on Euro Area Firms - Ursel Baumann; Annalisa Ferrando; Dimitris Georgarakos; Yuriy Gorodnichenko; Timo Reinelt (Institute of Labor Economics (IZA), 2024)
This paper provides new survey evidence on firms' inflation expectations in the euro area. Building on the ECB's Survey on the Access to Finance of Enterprises (SAFE), we introduce consistent measurement of inflation expectations across countries and shed new light on the properties and causal effects of these expectations. We find considerable heterogeneity in firms' inflation expectations and show that firms disagree about future inflation more than professional forecasters but less than households. We document that differences in firms' demographics, firms' choices and constraints, and cross-country macroeconomic environments account for most of the variation in inflation expectations by roughly equal shares. Using an RCT approach, we show that firms update their inflation expectations in a Bayesian manner. Moreover, they revise their plans regarding prices, wages, costs and employment in response to information treatments about current or future inflation.
Keywords: E20; E31; E52; 330; inflation expectations; firm decisions; price setting; surveys; randomised controlled trial